A South African exploration into outdoor adventure education and adolescent psychosocial development. Issue 5 (2nd September 2020) - Blaine, Judith; Akhurst, Jacqui
Abstract : This study explored the psychosocial outcomes of an outdoor adventure program for adolescents. A purposive sample of 144 Grade 10 learners participated in the Journey outdoor adventure education (OAE) programme (female = 48.6%, black = 27.5%; mean age =16.5 years; SD = 3.45 years). Applying a pre- and post-test quasi-experimental design, the adolescents completed self-report measures (including the Life Effectiveness Questionnaire, Emotional Literacy Questionnaire, and Connor-Davidson Resilience Scale) at three points in time: pre- and post- Journey, and four months later. Results following ANOVA analysis indicated increases in the adolescents' self-reports of life effectiveness and resilience (but not of emotional literacy) on completion of the programme. Findings suggest that a strength-based OAE would enhance psychosocial outcomes of adolescent school learners.